2016
DOI: 10.1534/genetics.116.192427
|View full text |Cite
|
Sign up to set email alerts
|

Commonalities in Development of Pure Breeds and Population Isolates Revealed in the Genome of the Sardinian Fonni's Dog

Abstract: The island inhabitants of Sardinia have long been a focus for studies of complex human traits due to their unique ancestral background and population isolation reflecting geographic and cultural restriction. Population isolates share decreased genomic diversity, increased linkage disequilibrium, and increased inbreeding coefficients. In many regions, dogs and humans have been exposed to the same natural and artificial forces of environment, growth, and migration. Distinct dog breeds have arisen through human-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 65 publications
3
36
0
Order By: Relevance
“…Additionally, seven local landrace populations, defined as distinct dog varieties unique to a specific geographic region with historically limited breeding populations, are included in this study. The latter are not recognized by any purebred canine registry but, nonetheless, may display a genetic pattern consistent with other purebreeds (Alam, Han, Lee, Ha, & Kim, ; Puja et al., ; Tanabe, ; Wijnrocx, Francois, Stinckens, Janssens, & Buys, ; Yoo et al., ), such as has been observed for one Italian regional population, the Fonni's Dog (Dreger, Davis, et al., ; Dreger, Rimbault, et al., ; Sechi et al., ). By focusing our analyses on breeds with diverse phenotypes that have all originated in a single country, we aim to employ genetic data to expand upon historical breed formation accounts and define the modes by which humans have produced recognizable and diversified dog breeds.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…Additionally, seven local landrace populations, defined as distinct dog varieties unique to a specific geographic region with historically limited breeding populations, are included in this study. The latter are not recognized by any purebred canine registry but, nonetheless, may display a genetic pattern consistent with other purebreeds (Alam, Han, Lee, Ha, & Kim, ; Puja et al., ; Tanabe, ; Wijnrocx, Francois, Stinckens, Janssens, & Buys, ; Yoo et al., ), such as has been observed for one Italian regional population, the Fonni's Dog (Dreger, Davis, et al., ; Dreger, Rimbault, et al., ; Sechi et al., ). By focusing our analyses on breeds with diverse phenotypes that have all originated in a single country, we aim to employ genetic data to expand upon historical breed formation accounts and define the modes by which humans have produced recognizable and diversified dog breeds.…”
Section: Introductionmentioning
confidence: 85%
“…High‐density, genome‐wide breed phylogeny analysis has been applied to well‐established dog breeds to elucidate the complex structure of breed relationships and their development (Dreger, Davis, et al., ; von Holdt et al., ; Mortlock, Khatkar, & Williamson, ). The largest phylogenetic study reported to date includes 161 dog breeds and over 1,300 dogs, consisting of 23 cladistic groupings based on genetic similarities (Parker et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genotype calls were made with Genome Studio V2011.1 with genotyping module v1.9.4 (Illumina). Subsets of these data were described in Dreger et al (Dreger et al, 2016a; Dreger et al, 2016b). The dataset consists of 938 dogs from 127 breeds and nine wild canids.…”
Section: Methodsmentioning
confidence: 99%